An exploration of sharing economy market segment structure: a case study of Airbnb. (4th February 2020) - Zhu, Qing; Wu, Yiqiong; Li, Yuze; Pan, Bing
The sharing economy has experienced rapid development in the past few years; nonetheless, at present, it is still in its infancy. As the sharing economy harnesses an innovative, novel business model, traditional marketing countermeasures are insufficient. Therefore, the sharing economy market patterns need to be explored and appropriate marketing countermeasures developed. To this end, text mining was applied to reviews on a typical sharing economy platform, Airbnb, to accomplish market segmentation. The results suggested that the host is the most valued factor to Airbnb guests. Thus, different from traditional hotel industry, it is essential for emerging peer-to-peer accommodation platform to encourage host to establish good interaction between the guests and the hosts. Meanwhile, cleanliness and convenience are also two major concerns to Airbnb guests, which indicates that Airbnb platform should encourage hosts to promote hotel-like properties for Airbnb listings. In addition, there is no strong evidence of heterogeneity in guests seeking accommodation in different locations.